Americus Felix Secundus Survey (1837) - John F. Wathen, Surveyor (1837)
Copy of page from John Wathen survey book. "This plat represents part of America Felix Secundus that part south of the road from the bridge to St. Lawrences Run and a small piece of Wrangelfield near Geo Morgans lot" Shows early layout of Leonardtown and Brittons Bay with buildings including church and courthouse. Also dwelling of H. G. S. Key (later Tudor Hall). Survey was done at the request of H. G. S. Key.